The Effect of Digital Interaction on the Level of Cyber ​​Dating Abuse in Generation Z - Dwi Yanti, Prita; Sardin; Fajria Utami, Nindita (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
This study examines the effect of digital interaction on the level of cyber dating abuse that often occurs in generation Z. The aims of this research are to examine and analyze how much influence digital interaction has on the level of cyber dating abuse, and to explain what factors are involved. affect Cyber ​​Dating Abuse can occur. The method used in this study is survey research with a quantitative approach, with the respondent population, namely students belonging to the Z generation. In the current era, technological advances have affected the way people interact into Digital Interaction, which does not rule out the possibility of influencing various negative behaviors. such as Cyber ​​Dating Abuse, through several actions such as controlling, demeaning, to bring down a partner in a relationship. There are several things that can be a factor in the occurrence of Cyber ​​Dating Abuse, including experiences of violence, jealousy, low social media ethics and lack of digital literacy. The results show that Digital Interaction has a significant effect on Cyber ​​Dating Abuse.